Protective effect of Schistosoma japonicum eggs on TNBS-induced colitis is associated with regulating Treg/Th17 balance and reprogramming glycolipid metabolism in mice - Hou, Xiao; Zhu, Feifan; Zheng, Wenwen; Jacques, Muziazia Lupemba; Huang, Jin; Guan, Fei; Lei, Jiahui (Frontiers in Cellular and Infection Microbiology, 2022)
Inflammatory bowel diseases (IBDs) have been classified as modern refractory diseases. However, safe, well-tolerated, and effective treatments for IBDs are still lacking. Therefore, there is an urgent need to develop novel therapeutic targets with fewer undesirable adverse reactions. A growing body of research has shown that infection with live helminths or exposure to defined helminth-derived components can downregulate pathogenic inflammation due to their immunoregulatory ability. Here we were to explore the protective role of Schistosoma japonicum eggs on murine experimental colitis caused by trinitrobenzene sulfonic acid (TNBS) and the underlying mechanism. Frequencies of splenic Treg and Th17 cells were detected by flow cytometry. Protein and mRNA expressions of Foxp3 and RORγt were investigated by Western Blot and quantitative real-time polymerase chain reaction (qPCR), respectively. Concentrations of transforming growth factor-beta1 (TGF-β1), interleukin-10 (IL-10) and IL-17A were assessed with ELISA. Expression levels of genes related to glycolipid metabolism were measured with qPCR. The results showed that pre-exposure to S. japonicum eggs contributed to the relief of colitis in the TNBS model, evidenced by improved body weight loss, reversing spleen enlargement and colon shortening, and decreased histology scores. Compared with the TNBS group, the TNBS+Egg group had increased Treg immune response, accompanied by decreased Th17 immune response, leading to the reconstruction of Treg/Th17 balance. In addition, a ratio of Treg/Th17 was correlated negatively with the histological scores in the experiment groups. Furthermore, the regulation of Treg/Th17 balance by S. japonicum eggs was associated with inhibiting the glycolysis pathway and lipogenesis, along with promoting fatty acid oxidation in the TNBS+Egg group. These data indicate that S. japonicum eggs have a protective effect against TNBS-induced colitis, which is related to restoring Treg/Th17 balance and regulating glucose and lipid metabolism.